Effects of brassinolide and anti-transpirants under water stress conditions on plant growth and physico-chemical changes of Musa acuminata colla cv. Berangan - Zakaria, Md Aiman Takrim (2018)
Banana (Musa acuminata) cv. Berangan relatively sensitive to dry soil condition which may influence good performance of growth, physiology and biochemical changes of banana. Global water supply crisis and uneven distribution of rainfall are some of limiting factors in agriculture sector for production of banana under Malaysia climate condition. The study was aimed to investigate the plant growth, physiology and biochemical changes on yield of banana as influenced by brassinolide (BR) and minerals solely or in combination under water stress conditions. BR represents one of the plant growth regulators essential in multiple developmental processes in plants including cell division, cell elongation and also reproductive development. One month old banana seedlings were transplanted into the 15 cm × 15 cm size of polybag and placed under rain shelter. Banana seedlings were foliar sprayed with different concentrations of BR (0, 3, 6 and 12 gL-1) for every two weeks intervals. The results showed that, BR concentration gave significant effects on the growth and physiology of banana plant (Musa acuminata cv. Berangan). As the BR concentrations increased from 0 to 6 gL-1, plant height, pseudo-stem diameter, total leaf numbers, total leaf area, fresh and dry weight of shoot were markedly increased from week 3 to week 8 after transplanting. The BR-induced increase in chlorophyll content which contributed the increase in photosynthesis rate. The root size and distributions were, however, not significantly affected by BR. However, exogenous application of BR at 6.88 gL-1 was the best concentration for banana plant at nursery stage as it was able to increase the plant height, pseudo-stem diameter, total leaf numbers and total leaf area of the species. Additionally, water stress or synonym referring to the drought season is the major abiotic stress which affect growth, physiology and biochemical activity in plant and cause major losses to agriculture production sector. The impacts of water stress in combination with exogenous application of plant growth regulator and minerals were also studied under rain shelter and open field plot. Under rain shelter experiment, one week old banana seedlings were transplanted in the polybag and the plants were grown under optimized concentration of BR (6.88 gL-1) from previous experiment. The leaves of the whole banana seedlings were foliar sprayed with three treatments: (i) BR as control, (ii) CaCO3 + MgCO3 (1:1, v/v) and (iii) BR + CaCO3 + MgCO3 (1:1:1, v/v). The solutions for BR, CaCO3 and MgCO3 were prepared by dissolving 6.88 g, 3.96 g and 0.23 g into 1 Litre (L) of distilled water, respectively. The plants were also subjected to water stress treatments: 50%, 75% and 100% of the FC. Water stress at 50% FC had significantly reduced major growth parameters (plant height, pseudo-stem diameter and total leaf area) but enhanced accumulation of proline and malondialdehyde content in leaves tissue. Concurrently, two months old banana seedlings were transplanted at open field plot in Field 15, Faculty of Agriculture, UPM. The similar treatments [(i) 6.88 gL-1 BR as control, (ii) CaCO3 + MgCO3 and (iii) BR + CaCO3 + MgCO3] were applied at every 2 weeks interval from 2 months after transplanting until flowering stage. Banana plants have been subjected to two different water regimes: (i) rain-fed and (ii) irrigated by micro-sprinkler system as control treatment for a continuous periods about 12 months. According to the results showed that, banana plants grown under rain-fed condition significantly reduced morphological characters such as plant height, pseudo-stem, canopy diameter, but enhanced accumulation of proline and malondialdehyde content in leaves tissue. Overall, the results proved that both conditions of water stress (50% FC) and rain-fed were significantly reduced major growth parameters (plant height, pseudo-stem diameter, total leaf area and canopy diameter), but enhanced accumulation of proline and malondialdehyde content in leaves tissue, respectively. These results suggest that application of BR + CaCO3 + MgCO3 on banana leaves increased vapour pressure deficit but reduced stomata conductance. Foliar application of BR with combination of CaCO3 and MgCO3 is recommended to regulate mechanism of drought adaptation to Berangan banana plant under field condition that facing global water supply criss and uneven distribution of rainfall, without negative effect on the harvested yield.